Rivers of Evidence - Clive Adams (Kerman University of Medical Sciences, 2013)
There has been too much of a one-way flow drift down a river of evidence. Researchers from rich countries have produced the primary evidence which they proceed to summarise within reviews. These summaries have directed care worldwide. However, things are changing and the river of evidence can flow in the other direction. The care of women with eclampsia has been changed or refined throughout the world because of a large low and middle income country trial. The global care of people with heart disease has been greatly modified by studies originating in China. The care of people who are acutely aggressive because of psychosis has to be reconsidered in the light of the evidence coming from Brazil and India. Healthcare is an issue everywhere and evaluation of care is not the premise of any one culture-the evidence-river must run both ways